Linux administration bootcamp : go from beginner to advanced - Cannon, Jason (Packt Publishing, 2018)
"This course will teach you the fundamentals of Linux Administration in depth, with practical examples. You will be guided step-by-step using a logical and systematic approach. As new concepts, commands, or jargon are encountered, they are explained in plain language, making it easy for you to understand."--Resource description page